Operatic album containing six songs for bass voice selected from standard and modern operas - BELLINI (G. Ricordi)
Vi ravviso, o loughi ameni (la sonnambula)nSi la rigueur et la vengeance (la juive)nVecchia zimarra, senti (la boheme)nElla giammai m'amo (don carlo)nLe veau d'or est toujours debout (faust)nVous qui faites l'endormie (faust)